PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN PERIODE 2016 – 2018 - Irine Melyani; Martha Ayerza Esra (Jurnal Ilmiah Manajemen & Bisnis, 2021)
The movement of stock price index is the important indicator for investors to determine whether the investor would sell, buy, or hold shares. The movement of CSPI is affected by several factor like macroeconomy. The purpose of this study was to determine the effect of inflation, interest rate, and exchange rate against CSPI. Theoretically, the effect of inflation, interest rate, and exchange rate is based on efficient market hyphothesis and signalling theory which inflation, interest rate and exchange rate provide signal to investor which affect their decision that cause change to CSPI. The type of data used in this study is secondary data with quantitative approach. The sampling is based on time series data from 2016-2018 using purposive sampling methodso that 36 samples are obtained. This research uses multiple uses multiple regression analysis method using SPSS 2.2. The results of this study indicate that during the period 2016-2018 inflation does not affect CSPI, the interest rate have negative affect on CSPI and exchange rate have positive affect on CSPI. Future research is expected to add another independent variable and extend the time range of the research to obtain ore accurate and comprehensive results. Keywords: Inflation, Interest Rate, Exchange Rate, Composite Stock Price Indonesia